In vitro regeneration of some economically important elite Indica rice genotypes - Swain, Alaka; Dash, Manaswini; Molla, Kutubuddin Ali; Behera, Deeptirekha; Baig, Mirza Jaynul; Dash, Bisnu Prasad (ORYZA-An International Journal of Rice, 2018)
Rice is an inherent part of human civilization and consumed by majority of Asians as their staple food. In addition to classical plant breeding methods, biotechnological tools including genetic engineering and genome editing are important for rice improvement to meet the growing demand. Both genetic engineering and genome editing technology are dependent on in vitro tissue culture and regeneration. Indica rice genotypes are widely known as recalcitrant in in vitro culture system. In the present study, we evaluated tissue culture responsiveness of 20 Indica rice genotypes known for important characters and standardized the suitable hormone combination for regeneration of each of those genotypes. Regenerated plantlets were successfully rooted and were acclimated to ex vitro condition. ISSR fingerprinting revealed monomorphic banding pattern between regenerated and control plants indicating the suitability of those regeneration media to maintain genetic fidelity. Results of the present study could be used efficiently in genetic transformation studies of Indica rice, which in turn would accelerate the rice crop improvement.